The International Mood Network (IMN) Nosology Project: differentiating borderline personality from bipolar illness. (9th September 2016) - Vöhringer, P. A.; Barroilhet, S. A.; Alvear, K.; Medina, S.; Espinosa, C.; Alexandrovich, K.; Riumallo, P.; Leiva, F.; Hurtado, M. E.; Cabrera, J.; Sullivan, M.; Holtzman, N.; et al.
Abstract : Objective: The differential diagnosis of bipolar illness vs. borderline personality is controversial. Both conditions manifest impulsive behavior, unstable interpersonal relationships, and mood symptoms. This study examines whether and which mood clinical features can differentiate between both conditions. Method: A total of 260 patients (mean ± standard deviation age 41 ± 13 years, 68% female) attending to a mood clinic were examined for diagnosis of bipolar illness and borderline personality disorder using SCID‐I, SCID‐II, and clinical mood criteria extracted from Mood Disorder Questionnaire (MDQ). They were analyzed using diagnoses as dependent variables. Predictors of bipolar and borderline diagnoses were identified by multivariable logistic regressions, and predictive validity of models was assessed using ROC curve analysis. Results: Bipolar illness was strongly predicted by elevated mood (OR = 4.02, 95% CI: 1.80–9.15), increased goal‐directed activities (OR = 3.90, 95% CI: 1.73–8.96), and episodicity of mood symptoms (OR = 3.48, 95% CI 1.49–8.39). This triad model predicted bipolar illness with 88.7% sensitivity, 81.4% specificity, and obtained an auROC of 0.91 (95% CI: 0.76–0.96) and a positive predictive value of 85.1%. For borderline personality disorder, only female gender was a statistically significant predictor (OR = 3.41, 95% CI: 1.29–13.7), and the predictive model obtained an auROC of 0.67 (95% CI: 0.53–0.74). Conclusion: In a mood disorder clinic setting, manic criteria and episodic mood course distinguished bipolar illness from borderline personality disorder.